Major Scientific Hurdles in HIV Vaccine Development: Historical Perspective and Future Directions - Ng’uni, Tiza; Chasara, Caroline; Ndhlovu, Zaza M. (Frontiers in Immunology, 2020)
Following the discovery of HIV-1 as a causative agent of AIDS, the expectation was to rapidly develop a vaccine; but thirty years later, we still do not have a licensed vaccine. Progress has been hindered by the extensive genetic variability of HIV and our limited understanding of immune responses required to protect against HIV acquisition. Nonetheless, valuable knowledge accrued from numerous basic and translational science research studies and vaccine trials have provided insight into the structural biology of the virus, immunogen design and novel vaccine delivery systems that will likely constitute an effective vaccine. Furthermore, stakeholders now appreciate the daunting scientific challenges of developing an effective HIV vaccine, hence the increased advocacy for collaborative efforts among academic research scientists, governments, pharmaceutical industry, philanthropy and regulatory entities. In this review, we highlight the history of HIV-1 vaccine development efforts, highlighting major challenges and future directions.